2013
DOI: 10.7314/apjcp.2013.14.10.6131
|View full text |Cite
|
Sign up to set email alerts
|

Determination of HER2 Gene Amplification in Breast Cancer using Dual-color Silver Enhanced in situ Hybridization (dc-SISH) and Comparison with Fluorescence ISH (FISH)

Abstract: Background: The two basic methods that are currently accepted to identify the HER2 status are immunohistochemistry and flyorescence in situ hybridization (FISH) . The aim of this study was to perform the dual-color silver in situ hybridization (dc-SISH) technique as an alternative to FISH. Materials and Methods: A total of 40 invasive breast carcinoma cases were assessed for HER2 gene amplification by FISH and dualcolor SISH. Results: Significant correlation was found in the HER2 expression results obtained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Adjuvant therapy using a monoclonal antibody against HER2 protein (Trastuzumab) is effective alone and in combination with conventional cytotoxic chemotherapy in patients whose breast carcinomas have amplification of HER2 (Goldenberg, 1999;Shak et al, 1999;PiccartGebhart et al, 2005;Romond et al, 2005;Duman et al, 2012;Tai et al, 2013;Unal et al, 2013). However, the significance of HER2 overexpression and amplification in the initiation and progression of ovarian mucinous carcinoma is less well understood (Weroha et al, 2011), and the treatment with HER2 antagonists has been disappointing (Bookman et al, 2003;Frederick et al, 2009).…”
Section: Her2 Expression In Ovarian Mucinous Carcinomas In Tunisiamentioning
confidence: 99%
See 3 more Smart Citations
“…Adjuvant therapy using a monoclonal antibody against HER2 protein (Trastuzumab) is effective alone and in combination with conventional cytotoxic chemotherapy in patients whose breast carcinomas have amplification of HER2 (Goldenberg, 1999;Shak et al, 1999;PiccartGebhart et al, 2005;Romond et al, 2005;Duman et al, 2012;Tai et al, 2013;Unal et al, 2013). However, the significance of HER2 overexpression and amplification in the initiation and progression of ovarian mucinous carcinoma is less well understood (Weroha et al, 2011), and the treatment with HER2 antagonists has been disappointing (Bookman et al, 2003;Frederick et al, 2009).…”
Section: Her2 Expression In Ovarian Mucinous Carcinomas In Tunisiamentioning
confidence: 99%
“…The HER2 gene is involved in intracellular signaling transduction pathways leading to cell growth and differentiation (Di Fiore et al, 1987;Kauraniemi et al, 2006;Unal et al, 2013). Studies have suggested that abnormal expression of HER2 gene by mutation or amplification may play an important role in tumor genesis (Auersperg et al, 2001;Garcia-Velasco et al, 2008;Cuadros and Villegras, 2009;Moatter et al, 2011;Duman et al, 2012;Pazhoomand et al, 2013;Unal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes methods of dual-color in situ hybridization (DISH) [28,39,40] in which HER2 status is typically determined by detecting HER2 gene copies with silver ISH and chromosome 17 copies with chromogenic red ISH. This gives the pathologists the benefit of counting copies of chromosome 17 and HER2 genes on the same slide in light microscopes that permit concurrent analysis of tissue morphology.…”
Section: Introductionmentioning
confidence: 99%